The government of money : monetarism in Germany and the United States - Johnson, Peter A. (Peter Andrew) (Cornell studies in political economy., 1998)
In recent years governments have increasingly given their central banks the freedom to pursue policies of price stability. In particular, the German Bundesbank and the U.S. Federal Reserve have been widely considered models of autonomous policymaking. This book traces the origins of their success to the political struggle to adopt monetarism in Germany and the United States.